2019
DOI: 10.5194/os-15-1531-2019
|View full text |Cite
|
Sign up to set email alerts
|

The life cycle of submesoscale eddies generated by topographic interactions

Abstract: Persian Gulf Water and Red Sea Water are salty and dense waters flowing at intermediate depths in the Gulf of Oman and the Gulf of Aden, respectively. Their spreading pathways are influence by mesoscale eddies that dominate the surface flow in both semi-enclosed basins. In situ measurements combined with altimetry indicate that Persian Gulf Water is stirred in the form of filaments and submesoscale structures by mesoscale eddies. In this paper, we study the formation and the life cycle of intense submesoscale … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…After exiting the marginal seas, the RSW and PGW outflows mix with the surrounding water masses in the Gulf of Aden and in the Gulf of Oman, respectively, then, the RSW plume stabilizes at 600-1000 m and the PGW plume at a 250-350 m depth [15][16][17]. Due to the influence of mesoscale eddies or bottom topography [4,[18][19][20], the PGW or RSW outflows are destabilized and they often shed smaller-scale eddies (of radii ranging between 5 and 20 km). These eddies, formed at a depth near the coast, drift away into the open ocean, carrying their warm and salty waters (see [3,21,22] for the small RSW eddies, and [23][24][25] for the PGW eddies).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After exiting the marginal seas, the RSW and PGW outflows mix with the surrounding water masses in the Gulf of Aden and in the Gulf of Oman, respectively, then, the RSW plume stabilizes at 600-1000 m and the PGW plume at a 250-350 m depth [15][16][17]. Due to the influence of mesoscale eddies or bottom topography [4,[18][19][20], the PGW or RSW outflows are destabilized and they often shed smaller-scale eddies (of radii ranging between 5 and 20 km). These eddies, formed at a depth near the coast, drift away into the open ocean, carrying their warm and salty waters (see [3,21,22] for the small RSW eddies, and [23][24][25] for the PGW eddies).…”
Section: Introductionmentioning
confidence: 99%
“…Vertical mixing was parameterized with the KPP (K-profile parameterization) scheme [32]. This numerical model has been described and validated in [18].…”
mentioning
confidence: 99%
“…This strip subsequently rolled up into small cyclones in the lee of the cape, possibly via inertia and the D'Asaro mechanism (D'Asaro, 1988) and/or by centrifugal and barotropic shear instabilities (Srinivasan et al, 2019). Frictional generation of vorticity near the coast has been intensively studied, using idealized (Dong et al, 2007; Morvan et al, 2019; Srinivasan et al, 2019) and realistic (Contreras et al, 2019; Dong & McWilliams, 2007; Gula et al, 2019, 2015; McWilliams, 2019; Vic et al, 2015) numerical simulations. It has been identified as an efficient mechanism to form deep submesoscale vortices in gradient wind balance, with high values of | ζ / f | (Srinivasan et al, 2019), and a lens‐like shape (Morvan et al, 2019).…”
Section: Discussion On the Origin Of The Vortexmentioning
confidence: 99%
“…PGW is leaving the Gulf as a bottom current and Indian Ocean Surface Water (IOSW) is entering through the Strait of Hormuz to compensate the volume loss. The PGW stratifies in relatively shallow depth into the Gulf of Oman ( 250 m), mixes with ambient water due to mesoscale and submesoscale eddies (Morvan et al, ; Vic et al, ), and spreads into the Indian Ocean where PGW signatures can be found, for example, in the Bay of Bengal (Jain et al, ). Previous measurements showed that the outflow of the PGW does not follow a significant seasonal cycle and is relatively steady with only small variabilities one time scales of 2–3 weeks (Johns et al, ; Swift & Bower, ; Pous et al, ).…”
Section: Introductionmentioning
confidence: 99%